The Effects of Self Regulated Learning and Learning Creativity on Students' Learning Outcomes in Economics: Evidence from Grade 11 Phase F Students at SMA Negeri 5 Padang - Afril Yeni C Purba; Caterina Lo; Dessyta Gumanti (The Future of Education Journal, 2026)
This study aims to analyze the effect of self-regulated learning and learning creativity on the economics learning outcomes of Grade XI Phase F students at SMA Negeri 5 Padang. This study employed a quantitative approach using multiple linear regression analysis. The population consisted of 214 students, while the sample comprised 140 students selected using the Slovin formula with a proportionate random sampling technique. Data were collected through questionnaires and documentation. The research instruments were tested for validity and reliability, and the data were analyzed using IBM SPSS Statistics version 19. The results showed that self-regulated learning had a positive and significant effect on economics learning outcomes (Sig. = 0.009 < 0.05), learning creativity also had a positive and significant effect (Sig. = 0.025 < 0.05), and both variables simultaneously had a positive and significant effect on economics learning outcomes (F = 5.356, Sig. = 0.006 < 0.05). The coefficient of determination (R²) was 0.073, indicating that self-regulated learning and learning creativity contributed 7.3% to economics learning outcomes, while the remaining 92.7% was influenced by other factors. Therefore, improving self-regulated learning and learning creativity can support the improvement of students' economics learning outcomes.